2006
DOI: 10.1021/ie051206h
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Zinc(II) from Aqueous Solution by Purified Carbon Nanotubes:  Kinetics and Equilibrium Studies

Abstract: Single-walled carbon nanotubes (SWCNTs) and multiwalled carbon nanotubes (MWCNTs) were purified by sodium hypochlorite solutions and were employed as sorbents to study the kinetics and equilibrium of Zn2+ sorption from aqueous solution. The amount of Zn2+ sorbed onto CNTs increased with a rise in temperature. Using the same conditions, the Zn2+ sorption capacity of CNTs was much greater than that of commercially available powdered activated carbon, reflecting that SWCNTs and MWCNTs are effective sorbents. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(126 citation statements)
references
References 16 publications
5
119
1
1
Order By: Relevance
“…This would suggest that the current filter could be used in a faster stream whilst maintaining high efficiency (SI section S6). It would also be possible to have the same complete ion removal at higher injection rates by increasing the length of filter, alternatively increasing the temperature may also improve adsorption efficiency as was previously shown by Lu et al [32] for Zn 2+ .…”
Section: Metal Ion Removalmentioning
confidence: 87%
“…This would suggest that the current filter could be used in a faster stream whilst maintaining high efficiency (SI section S6). It would also be possible to have the same complete ion removal at higher injection rates by increasing the length of filter, alternatively increasing the temperature may also improve adsorption efficiency as was previously shown by Lu et al [32] for Zn 2+ .…”
Section: Metal Ion Removalmentioning
confidence: 87%
“…Moreover, it may cause extreme weakness, dermatitis, headache, dizziness and respiratory distress [6]. Zinc toxicity from excessive ingestion is less common, however, it may cause damage to various systems in the human body [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…CNTs were found to be superior sorbents for inorganic pollutants such as fluoride [18], and several divalent metal ions [7,8,[19][20][21][22][23][24][25]. Li et al [24] reported that CNTs with more defects and poor quality possess higher surface area and exhibit better lead sorption capacity compared to aligned CNTs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations